Quelle co-construction du projet de vie des enfants en situation de handicap ? Réceptions croisées par les professionnels et les parents - Anne Pellissier Fall; Matthieu Laville (Questions Vives)
For the past twenty years, the renewed context of social policies for children with disabilities has taken the form of working with families to create a more democratic relationship of assistance through an over-life project measure for their child. This perspective upsets the historical norms constituting the field of special education, based on the hierarchization of knowledge that tended to legitimize professional knowledge in favor of the knowledge of experience of families. Based on a secondary analysis of two studies, conducted with education and health professionals on the one hand, and with parents of disabled children on the other, this article aims to study the reception of this life project, considered here as an instrument of public action. Our analysis allows us to understand the processes of appropriation of this project by the various publics concerned, namely families and disability professionals.